Ni/CeO2 as catalyst for glycerol hydrogenolysis without external H2 supply: the role of synthesis conditions - Jarauta Córdoba, Clara; García Nieto, Lucía; Arauzo Pérez, Jesús; Ruiz Palacín, Joaquín; Oliva Alcubierre, Miriam (Jornada de Jóvenes Investigadores del I3A, 2018)
Aqueous phase processes at high pressure are considered one of the most promising thermochemical processes to valorize wet residual streams, in order to produce value-added chemicals. Among them, glycerol hidrogenolysis (HG) has been intensely studied. Although many different catalytic systems for HG have been studied in the last years, the Ni/CeO2 catalytic system has not been so deeply performed in liquid phase. This work studies the hydrogenolysis of glycerol without external H2 supply as a pathway to obtain value-added chemicals using Ni/CeO2 catalysts. Different synthesis parameters were changed, in order to determine their influence on the catalytic activity. In this process, 1,2–propanediol and ethylene glycol are produced, compounds which are valuable due to their use in chemical synthesis, antifreeze fluids, and others.